Social Inclusive Education Project (SIEP) as a Community for Handling Children with Special Needs in Rural Areas - Nur Azizah; Adhit Cahyo Prasetyo; Nur Dini; Vera Wulandari; Maisarah Kruesa (Indonesian Journal of Community and Special Needs Education, 2022)
Education is for everyone. This indicates that everyone deserves access to education either in urban areas or urban areas. The purpose of this study is to describe the handling of the Social Inclusive Education Project (SIEP) community for children with special needs in rural areas. Data collection techniques are used for observations and interviews with SIEP founders and volunteers. The results show that the SIEP community has carried out various treatments for special needs children in rural areas. An assessment was run by the volunteers before carried out the treatment. The handling is carried out after making the Individualized Education Program for each child with special needs, including down syndrome, motor barriers, specific learning difficulties, visual impairments, and speech delays. The children with special needs are given treatment according to the child's needs such as training to memorize the Qur’an, training in prayer procedures, the introduction of numbers and letters, training in pronunciation of vowels, reading storybooks, writing training, and swimming training. The effort and aid carried out by the SIEP community for children with special needs in rural areas are expected to be a reference for volunteering activities for children with special needs in Indonesia, Japan, Malaysia, Thailand, and other countries in the world.